The Iconography of Dr. B. R. Ambedkar: The Symbolic Means in Visual and Design Culture - Arun Mascarenhas (International Journal of Arts Architecture & Design)
The Iconography of Dr. Bhimrao Ramji Ambedkar (1891–1956) is a subject of significant scholarly interest, delving into various aspects of his life, work, and influence. Ambedkar’s impact on society, particularly formerly untouchable communities, has been a focal point in understanding the dynamics of caste, politics, and community life in India. His writings on Buddhism, social democracy, and the role of education in fostering democratic values have been subjects of in-depth analysis. Scholars have explored themes such as sovereignty, caste, agonism, Buddhism, politics, and the context of social and cultural practices surrounding his life, experiences, and decisions through an analytical lens. Studies have also shed light on Ambedkar’s iconography and its historical and political significance, tracing the evolution of his image and statues from a period predated by his current veneration. His iconography has been studied in the context of art, literature, and cultural productions, and it serves as a rich tapestry of historical, political, and sociocultural narratives. Still, his image and symbolism in contemporary society, reflected in multiple mediums and forms, have not been captured coherently. This study of selected contemporary creative works sheds light on symbolism, visual, and design culture, focusing on Ambedkar’s iconography with a relevant literature review.